Corn starch systems as carriers for yerba mate (Ilex paraguariensis) antioxidants - Deladino, Lorena (2015)
Corn starch's ability to bind and carry a yerba mate extract with strong antioxidant properties was explored in this paper. The starch was treated by high hydrostatic pressure to increase its loading capacity and scanning electron microscopy revealed that the high pressure treatment altered the shape of starch granules and changed their surface appearance. High pressure caused partial granule gelatinization as determined by calorimetric measurements, also increasing the granule specific surface area, as quantified by nitrogen adsorption. This increase in surface was due to the generation of pores, which favored the adsorption of the yerba mate hydrosoluble polyphenols. The yerba mate polyphenol concentration in the starch carriers was determined by HPLC-MS and its antioxidant activity was measured by the DPPH radical and photochemiluminiscense (PCL) methods. Treated starches incorporated a higher amount of yerba mate polyphenols, however, native starch could be an appropriate antioxidant carrier as well. Furthermore, it was found that the antioxidant activity was maintained after high pressure treatment without changing the yerba mate polyphenols profile.